2021
DOI: 10.3390/en14020451
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PV Power Forecasting Methods: A Comparison of Different Approaches

Abstract: Accurate photovoltaic (PV) prediction has a very positive effect on many problems that power grids can face when there is a high penetration of variable energy sources. This problem can be addressed with computational intelligence algorithms such as neural networks and Evolutionary Optimization. The purpose of this article is to analyze three different hybridizations between physical models and artificial neural networks: the first hybridization combines neural networks with the output of the five-parameter ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The article by Niccolai et al [40] analyzes the forecast accuracy of three hybrid models that integrate physical elements of the system with ANNs. The first model combines ANNs with the output of the five-parameter physical model of a photovoltaic module where the parameters are obtained from a data file.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The article by Niccolai et al [40] analyzes the forecast accuracy of three hybrid models that integrate physical elements of the system with ANNs. The first model combines ANNs with the output of the five-parameter physical model of a photovoltaic module where the parameters are obtained from a data file.…”
Section: Related Workmentioning
confidence: 99%
“…Although there are works that combine RNN techniques with statistical methods, such as ARMA, ARIMA, SAR-IMA, and Pearson's coefficients, among others ( [22,26,35]), in most cases, they do not use a large volume of data for model training and validation. In addition, few works were found that address this type of prediction through hybrid methods ( [34,40]).…”
Section: Related Workmentioning
confidence: 99%
“…Due to their intrinsic stochastic nature, RES can introduce instability in the electric network. Thus, a key element for obtaining a feasible energy transition is the capability to achieve a good forecasting of RES production and electric load [8]. Many works in the literature address the problem of either short-term [10] or long-term forecasting [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the recent developments in machine learning on the one hand and developments in smart meters to provide real data on the other hand make machine learning techniques quite popular for time series point forecast. Therefore, many researchers have focused on point forecast of PV generation 4,10‐12 . The point forecast provides the expected PV generation for each time step over the time horizon.…”
Section: Introductionmentioning
confidence: 99%